Collaborative Modeling of Use Case & Damage Scenarios in Online Workshops Using a 3D Environment. (May 2022) - Japs, S.; Schmidt, S.; Karg, F.; Kaiser, L.; Kharatyan, A.; Dumitrescu, R.
Abstract: The development of technical systems requires close cooperation of stakeholders from different disciplines. This collaboration takes place in workshops. Driven by digitalization and by the current pandemic such workshops take place primarily online. Suitable collaboration tools and methods are crucial to success. At the beginning of such workshops, use and damage scenarios are identified. In this paper, we presented a method and tool for identifying and modeling use and damage scenarios, which we evaluated in 14 online workshops with a total of 118 participants over a period of almost 3 years.